Comorbidity of PTSD in anxiety and depressive disorders: Prevalence and shared risk factors - Spinhoven, Philip; Penninx, Brenda W.; van Hemert, Albert M.; de Rooij, Mark; Elzinga, Bernet M. (Child abuse & neglect, 2014)
The present study aims to assess comorbidity of posttraumatic stress disorder (PTSD) in anxiety and depressive disorders and to determine whether childhood trauma types and other putative independent risk factors for comorbid PTSD are unique to PTSD or shared with anxiety and depressive disorders. The sample of 2402 adults aged 18–65 included healthy controls, persons with a prior history of affective disorders, and persons with a current affective disorder. These individuals were assessed at baseline (T0) and 2 (T2) and 4 years (T4) later. At each wave, DSM-IV-TR based anxiety and depressive disorder, neuroticism, extraversion, and symptom severity were assessed. Childhood trauma was measured at T0 with an interview and at T4 with a questionnaire, and PTSD was measured with a standardized interview at T4. Prevalence of 5-year recency PTSD among anxiety and depressive disorders was 9.2%, and comorbidity, in particular with major depression, was high (84.4%). Comorbidity was associated with female gender, all types of childhood trauma, neuroticism, (low) extraversion, and symptom severity. Multivariable significant risk factors (i.e., female gender and child sexual and physical abuse) were shared among anxiety and depressive disorders. Our results support a shared vulnerability model for comorbidity of anxiety and depressive disorders with PTSD. Routine assessment of PTSD in patients with anxiety and depressive disorders seems warranted.